Long‐term recovery of above‐ and below‐ground interactions in restored grasslands after topsoil removal and seed addition. Issue 9 (5th March 2022) - Resch, Monika Carol; Schütz, Martin; Ochoa‐Hueso, Raúl; Buchmann, Nina; Frey, Beat; Graf, Ulrich; van der Putten, Wim H.; Zimmermann, Stephan; Risch, Anita C.
Abstract: Evaluation of restoration activities is indispensable to assess the extent to which targets have been reached. Usually, the main goal of ecological restoration is to restore biodiversity and ecosystem functioning, but validation is often based on a single indicator, which may or may not cope with whole‐ecosystem dynamics. Network analyses are, however, powerful tools, allowing to examine both the recovery of various biotic and abiotic properties and the integrated response at community and ecosystem level. We used restoration sites where topsoil was removed from former intensively managed grassland and seeds were added. These sites were between 3 and 32 years old. We assessed how plants, soil biota, soil properties and correlation‐based interactions between biotic communities and their abiotic environment developed over time and compared the results with (i) intensively managed (not restored), and (ii) well‐preserved targeted semi‐natural grasslands. Plant, nematode, fungal and prokaryotic diversity and community structures of the restored grasslands revealed clear successional patterns and followed similar trajectories towards targeted semi‐natural grasslands. All biotic communities reached targeted diversity levels no later than 18 years post‐restoration. Ecological networks of intensively managed and short‐term (~4 years) restored grasslands were less tightly connected compared to those found in mid‐ and long‐term (~18–30 years) restored and target grasslands. Restoration specifically enhanced interactions among biotic communities, but reduced interactions between biotic communities and their abiotic environment as well as interactions among abiotic properties in the short‐ and mid‐term. Synthesis and applications : Overall, our study demonstrated that topsoil removal and seed addition were successful in restoring diverse, tightly coupled and well‐connected biotic communities above‐ and below‐ground similar to those found in the semi‐natural grasslands that were restoration targets. Network analyses proved to be powerful in examining the long‐term re‐establishment of functionally connected biotic communities in restored ecosystems. Thus, we provide an approach to holistically assess restoration activities by notably considering the complexity of ecosystems, much in contrast to most traditional approaches. Abstract : Overall, our study demonstrated that topsoil removal and seed addition were successful in restoring diverse, tightly coupled and well‐connected biotic communities above‐ and below‐ground similar to those found in the semi‐natural grasslands that were restoration targets. Network analyses proved to be powerful in examining the long‐term re‐establishment of functionally connected biotic communities in restored ecosystems. Thus, we provide an approach to holistically assess restoration activities by notably considering the complexity of ecosystems, much in contrast to most traditional approaches.